The effects of utilizing selected popular songs in developing language skills of english language students / Nora Md. Salleh , Roslina Mohd. Jani and Mahdalela Rahim - Md. Salleh, Nora; Mohd. Jani, Roslina; Rahim, Mahdalela (Institute of Research, Development and Commercialization, 2004)
This study aims to find out the effects of utilizing selected popular songs in developing students' language skills in English language classrooms. The main focus of the study is to utilize the songs in the skill of writing, particularly in the writing of argumentative essays and aims at providing variety to the present classroom teaching and learning. Argumentative essay writing is one aspect of writing taught in BEL 250 for Semester Three Diploma students of UiTM. This study also tries to determine students perception of the use of popular songs in the classroom. The study showed that teaching English language using popular songs as lead in activities give a positive effect in enabling students to write argumentative essays. There is also a positive effect on students' personal interest, opinion and attitude towards the use of popular songs as a teaching material in ESL classrooms.